Questions and challenges in establishing and maintaining a local studies center the case of the Cavite Studies Center of Dela Salle University-Dasmarinas - Calairo, Emmanuel Franco (2008)
Local collection building has become one of the major thrusts in university-based Philippine libraries because of the need to showcase local identity. Initially, this collection usually starts as part of the Filipiniana collection but as the number of materials increase and its organization becomes more complex, the apparent need arises to separate these materials from the Filipiniana section and to showcase the collection as one section of the library. In the early 1990's, some universities started to appreciate the value of local studies because Higher Education Institutions ( HEI's) and State Colleges and Universities (SUC's) in the Philippine were mandated to respond to the need of the immediate community especially in developing research programs and community extension projects. With this as a mandate, some universities responded by accumulating materials designed to orient the researches on the facts, issues, and problems confronted by the immediate community. 1 Other universities also took action by strengthening their local culture materials in their respective libraries. 2 However, such initiatives emanating from the library do not signify an adequate action to speed-up the local collection development. There has to be one academic unit in the university or school setting that should focus and specialize in this activity. Because of this need, the establishment of a local studies center has become an indispensable effort in developing local collection.
This paper is an attempt to explain the role of the local studies centers in the Philippines especially its distinct capacity to collect local materials. The discussion focuses on the questions and challenges in establishing and maintaining a local studies center. As a case in point, the paper shall zero in on the Cavite Studies Center of De La Salle University-Dasmarinas in Cavite, Philippines.